Islam Liberal: Menimbang Konteks, Merumuskan Penafsiran - Moh Shofan (Budapest International Research and Critics University, 2015)
The methodologies of liberal or progressive Islam rest on the interpretation and re-interpretation of traditional Islamic scripture (the Quran) and other texts (such as the Hadith), a process called ijtihad. This can vary from the slight to the most liberal, where only the meaning of the Quran is considered to be a revelation, with its expression in words seen as the work of the prophet Muhammad in his particular time and context. As a consequence, liberal/progressive Muslims may then interpret verses from the Quran allegorically or even set them aside.